2011
DOI: 10.1111/j.1442-2042.2011.02924.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin and endothelin in testicular ischemia reperfusion injury

Abstract: Abbreviations & AcronymsObjectives: To determine whether angiotensin and endothelin have any role in testicular ischemia reperfusion injury by investigating the effects of the angiotensin converting enzyme inhibitor enalapril, selective non-peptide angiotensin-II type I blocker losartan and dual endothelin receptor blocker bosentan. Methods: Rats were anesthetized with thiopental sodium (50 mg/kg i.p.) before the operation. The left testicular artery and vein of rats were occluded for 1 h; before the bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Furthermore, necrosis and degeneration of seminiferous tubule (N) can be noticed in the drug treated groups as shown in Fig 2 : (B and C arrows) as compared with spermatogenesis development which has been noticed on a sample from the control group and numerous spermatozoa are observed within the tubule lumen as observed in Fig 2 (A). These observations agreed with Turkili and others study in 2012 who reported ischemic alterations and maturation arrested in testicular tissue after using Enalapril [14].…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, necrosis and degeneration of seminiferous tubule (N) can be noticed in the drug treated groups as shown in Fig 2 : (B and C arrows) as compared with spermatogenesis development which has been noticed on a sample from the control group and numerous spermatozoa are observed within the tubule lumen as observed in Fig 2 (A). These observations agreed with Turkili and others study in 2012 who reported ischemic alterations and maturation arrested in testicular tissue after using Enalapril [14].…”
Section: Resultssupporting
confidence: 93%
“…In the testes, it has been reported that a local RAS is responsible for maintaining blood pressure and volume (59). During tIR injury, inhibition of the classical RAS pathway leads to reductions in testicular injury, inflammation and oxidative stress (10,60). Recently, the testicular angiotenis converting enzyme (tACE)/Ang-(1-7)/Mas receptor axis has been described and it has been suggested that Ang-(1-7)-mediated protection may increase nitric oxide (NO) bioavailability, inhibit ROS generation and suppress apoptosis in tIR (10).…”
Section: Interaction With Renin-angiotensin System (Ras)mentioning
confidence: 99%
“…Even with an immediate untwisting, the resultant damage causes subinfertility and infertility followed by loss of spermatogenesis and germ cell‐specific apoptosis (Mogilner et al ., ; Romero et al ., ; Saeedi Saravi et al ., ). Detrimental mechanism and mediators in testicular torsion/detorsion (T/D) are similar to ischaemia/reperfusion (I/R) injury (Turkili et al ., ).…”
Section: Introductionmentioning
confidence: 97%